Collaborative Public Diplomacy - Fisher, A. author. aut Link
XI, 260 p.
Keywords: Using archival research and recorded interviews, this book charts the development of American Studies in Europe during the early Cold War. It demonstrates how negotiations took place through a network of relationships and draws lessons for public diplomacy in an age when communities are connected through multi-hub, multi-directional networks.